Strengthening Society Participation on Planning The Development of a Religious Tourism Village Through Transparency, Accountability, Communication and Leadership - Akmala Hadita; Salman Rashid (Universitas Negeri Semarang, 2024)
Religious tourism villages have the potential to significantly boost local economies and foster cultural preservation. However, effective development planning in these villages often requires active community participation and robust governance mechanisms. This study was conducted to determine whether transparency, accountability, communication and leadership can optimize community participation in religious tourism village development planning. The object of the research was determined in Parentas Village, Cigalontang District, Tasikmalaya. Regression analysis using moderating variables was chosen as the method of data analysis for this kind of quantitative research. The findings demonstrated that community involvement significantly and favorably affects village development planning. The influence of community involvement on village development planning can be moderated and strengthened by transparency, accountability, communication, and leadership. The results of this study show that in order to maximize community participation in tourism village development planning, transparency, accountability, communication, and village government leadership are crucial considerations. the importance of this research being carried out, by increase community participation so that planning for the development of parental religious tourism villages will be better with transparency, accountability, communication and leadership is moderating. This study uniquely integrates the moderating effects of transparency, accountability, communication, and leadership on community participation in village development planning. By focusing on these governance mechanisms, the research provides new insights into optimizing community involvement in the context of religious tourism village development.